THE ARCHITECTURE AND THE PHENOMENON OF TRANSFFERING THE TECHNO LIGY WITHIN THE THEMES OF BOTH FORM AND MEANING (Journal of Engineering, 2003)
The world witnesses, a revolution of scientific and technological breakthroughs and the scientific progress in the field of materials, the launching on the market of new technolory for manufacturing and employing new elements in buildings, like transparent or opaque diaphragms and with all the sound and heat requirements. This new technology is characterized by substanceless, after it was fora long time consort with substantial, like information and communication technology and other developments, which indicate so many factors thatpvzzle the architects when reviewing the style of designing buildings. and making use of these possibilities and transforming them to develop the expressional force of architecture and improve its performance within its private environment. Themain issue is not that about transforming and import of shapes, materials and techniques, but it is a matter of education and civilization which opens the way to the future with great care to culture's individuality, because there is no effective education without civilized identity and there is no identity without intellectual production.